2011
DOI: 10.1614/wt-d-10-00146.1
|View full text |Cite
|
Sign up to set email alerts
|

MCPA Synergizes Imazamox Control of Feral Rye (Secale cereale)

Abstract: Field, greenhouse, and laboratory studies were conducted to determine the effect of MCPA ester, fertilizer type, and fertilizer rate on feral rye control with imazamox. In field studies near Sidney, NE, increasing the concentration of liquid ammonium phosphate (10–34–0) from 2.5 to 50% of the spray solution decreased feral rye control with imazamox by as much as 73%. Conversely, adding MCPA ester to imazamox significantly increased feral rye control in field studies by up to 77%. Initial greenhouse studies con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Absorption data were fit to an asymptotic, exponential, maximum‐two‐term model as the following equation: where y is the percentage absorption expressed as a percentage of the applied dose, a is the upper asymptote, or theoretical absorption maximum, x is time, expressed as hours after treatment, and b is a slope term that has a positive relationship to the rate with which absorption reaches maximal levels. Identical regression analysis has been used to model absorption of imazamox in feral rye to understand MCPA‐ester/imazamox synergism 33…”
Section: Methodsmentioning
confidence: 99%
“…Absorption data were fit to an asymptotic, exponential, maximum‐two‐term model as the following equation: where y is the percentage absorption expressed as a percentage of the applied dose, a is the upper asymptote, or theoretical absorption maximum, x is time, expressed as hours after treatment, and b is a slope term that has a positive relationship to the rate with which absorption reaches maximal levels. Identical regression analysis has been used to model absorption of imazamox in feral rye to understand MCPA‐ester/imazamox synergism 33…”
Section: Methodsmentioning
confidence: 99%
“…For example, the AR model was far more likely to be the better model for the Kniss (2006) data set compared with the RHB model based on AICc, and the AR model provided A max estimates of 69 to 73%, which were very similar to the maximum absorption observed in that study (67 to 70%); conversely, the RHB model provided A max estimates of 91 to 96%, far greater than any absorption value that was observed in the study. Similarly, the RHB model provided a better description of the Kniss et al (2011) data set, and the A max estimates were more similar to the observed maximum absorption values for each treatment compared with the AR model.…”
Section: Model Comparisonmentioning
confidence: 64%
“…To determine which model best describes foliar herbicide absorption, 10 herbicideabsorption data sets were analyzed using the AR model (Equation 4) and the RHB model (Equation 9). Raw data were used for four of the data sets (Bukun et al 2009(Bukun et al , 2010Kniss 2006;Kniss et al 2011). For the remaining 6 data sets, treatment means reported in the published articles were used (Everman et al 2009a,b;Frihauf et al 2010;Hennigh and Al-Khatib 2010;Schuster et al 2007;Weinberg et al 2007).…”
Section: Comparison Of Models For Herbicide Absorptionmentioning
confidence: 99%
See 2 more Smart Citations